Characteristics and functional properties of purple corn (Zea mays L.) var. subnigroviolaceo (Scientia Agropecuaria, 2014)
Zea Mays L. variety purple (purple corn) is a plant native of America, which has the episperm seeds (grains) and the cobs (cob) in purple, which gives special characteristics to the pigments that have (between 1.5% and 6.0%), called anthocyanins, which belong to the group of flavonoids. Due to its high content of anthocyanins (cianin C3G-3-glucose as its main color) and phenolic compounds act as powerful natural antioxidant and anticancer, Further having functional properties due to these bioactive compounds. The purple corn also provides significant amounts of starch, about 80% (complex carbohydrate), 10% of sugars provide sweetness, up to 11% protein, up to 2% minerals and B vitamins and ascorbic acid, concentrated in endosperm (grain free envelope). Also the nutritional value, the purple corn has a rich composition of phytochemicals, which have beneficial effects on our body, such as neutralize free radicals and act as antimutagenic. His review paper aimed to collect information on the studies undertaken to purple corn as an alternative to artificial food dyes and health benefits when included in the diet. Benefits such as cardiovascular diseases (hypertension), lowering cholesterol, fighting diabetes, being the most remarkable antioxidant action (wrinkle).
Keywords: Anthocyanin; Flavonoid; Phytochemical; Functional properties; Bioactive Compound